Geology of Hebes Chasma, Mars: 1. Structure, Stratigraphy, and Mineralogy of the Interior Layered Deposits. Issue 11 (5th November 2018) - Schmidt, Gene; Fueten, Frank; Stesky, Robert; Flahaut, Jessica; Hauber, Ernst
Abstract: Hebes Chasma is an 8‐km deep, 126 by 314 km, isolated basin that is partially filled with massive deposits of water‐altered strata called interior layered deposits (ILDs). By analyzing the ILD's structure, stratigraphy, and mineralogy, a depositional history of Hebes Chasma is interpreted. Three distinct ILD units were found and are informally referred to as the Lower, Upper, and Late ILD. These units are distinguished by their layer thicknesses, layer attitudes, mineralogies, and erosional landforms. The Lower and Upper ILDs comprise the chasma's 7.5‐km tall, 120 by 43 km, central mound, and the Late ILD is located in the valley between the central mound and the chasma's northern wall. A horizontal unconformity separates the Lower and Upper ILDs, and layer attitudes revealed large‐scale shallow folding within the Lower ILD. All ILDs are characterized by both monohydrated and polyhydrated sulfates signatures. Erosional landforms such as hummocks, polygons, and debris flows suggest past glacial activity within the chasma. A scenario involving several ash fall events during various stages of chasma formation is proposed as the dominant setting throughout Hebes' geologic history. Plain Language Summary: On the planet Mars there is a large 4, 000 km‐long system of 12 canyons called Valles Marineris. On Mars these canyons are called chasmata or individually a chasma. Some are linked together, while some are isolated, but all are considered to share the same origins of formation. Within the interiors of several chasmata are large layered mounds up to 8‐km thick. The origins of these layered mounds are elusive, but there are several contending theories that typically consider them to have been made after or during the chasmata formation. Detections from orbital instruments show that these mounds also contain abundant hydrated minerals that could have only been formed in the presence of water. One particular chasma called Hebes is the topic of this paper and its large layered mound has been measured and described using several different methods to help constrain the geologic history of Valles Marineris. The mound within Hebes was discovered to have three units formed in three separate depositions. These units differ in their mineralogies, layer thicknesses, layer attitudes, and erosional features. A geologic map of Hebes Chasma was created, and stages of deposition are described. Key Points: Three separate ILD units and an unconformable contact were identified The ILD units have unique mineralogies, layer thicknesses, and layer attitudes New geologic map, cross section, and depositional historyis presented